Penerapan Media Belajar Berbasis Digital Google Site Dalam Pembelajaran Lingkungan - Novfirman, Novfirman; Romy Aulia (PT. Padang Tekno Corp, 2023)
Information technology-based learning has become important in the world of modern education. In this digital era, Google has become a service that almost everyone must have. However, in practice, there is a problem with the various conveniences that Google offers, which are open source and should be used as a solution in the transformation of conventional learning environments to digital learning. This research aims to develop Google Site-based digital learning media as a solution to the transformation of conventional learning to digital learning. The R&D method involves needs analysis, media development, UI/UX evaluation, and increasing learningefficiency. The study population consisted of 30 lecturers and students from the Plantation Management Study Program, with 27 people as samples using the random sampling method and Krejcie and Morgan table calculations. The results of the study show the high need for digital media in the post-pandemic era, where online learning is dominant. The development and implementation of open-source Google site-based learning media increases learning efficiency compared to the direct presentation of material through online presentations. The accessibility and features provided by the Google site add value to the UI and UX evaluation for users.